PERAN SISTEM INFORMASI AKUNTANSI PADA UMKM PENGRAJIN ANYAMAN BAMBU - Ni Nyoman Sri Rahayu Trisna Dewi; Komang Fridagustina Adnantara; Tiara Kusuma Dewi (Universitas Triatma Mulya, 2022)
Tanggahan Peken is one of the areas in Bangli which famous for its bamboo crafts. Most of the people of Tanggahan Peken have the skills of making bamboo crafts. The partner in this activity is Wulans Bambu which is an economically productive partner. Bamboo craft shows the development of the crafts all the time because these products have a broader function, which is not only used in religious ceremonies but also started to be used for daily utensils. The main problem in this research was the marketing management which still used conventional systems, even though the opportunity for showing their products to outside Bali was very large. The solution offered is to introduce the role of accounting information systems in the form of websites and e-commerce for the partners in terms of marketing and electronic transactions as well as providing assistance on export procedures and export requirements so they could enter foreign markets without going through third parties. The outputs that targeted for this activity is an increase in partner empowerment in terms of increasing partner knowledge, partner success in expanding marketing reach, and increasing partner turnover.